LANGUAGE ATTITUDES OF MEMBERS OF THE LAMPUNG DPRD EDUCATION COMMISSION AND THEIR IMPLICATIONS FOR THE USE OF INDONESIAN IN EDUCATION POLICY PRODUCTS - Jupri, Jupri (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to describe the language attitudes of the members of the Regional House of Representatives (DPRD) Lampung Commission V in the field of education during the 2014–2019 period and their implications for the use of the Indonesian language in educational policy products. Method: The research employed a qualitative approach with data collection techniques including questionnaires, observations, interviews, and documentation. The data sources consisted of the language attitudes of DPRD Lampung Commission V members and educational policy documents, particularly Regional Regulation (PERDA) No. 9 of 2016. Results: The findings reveal that DPRD Lampung Commission V members exhibited a positive language attitude with a 65% score, reflecting loyalty, pride, and compliance in using the Indonesian language. This positive attitude is manifested in the use of the Indonesian language in the formulation of educational policy products, as seen in PERDA No. 9 of 2016. Novelty: This research provides a novel perspective by linking the language attitudes of policymakers to the linguistic quality of regional educational policies, highlighting the crucial role of language in shaping effective and inclusive educational regulations.